Bumblebee season : a novel - Garvin, Eileen (Dutton, 2026)
Beekeeper Jake Stevenson should be celebrating. His fledgling honey farm has been inundated with orders. Instead, Jake is worried. He can't seem to hire anyone--with local teens more interested in jobs at Hood River's hip waterfront--and there's no way he can do it all by himself, no matter how adept he's become at maneuvering among the beehives in his wheelchair. Meanwhile Flaco López, a young migrant from Mexico, is lost on Mount Hood when he stumbles upon Jake's beehives in a high alpine meadow. As Flaco takes refuge on Jake's farm, they begin to form a tentative friendship. And the two soon cross paths with Abigail Plue, a scientist more interested in insects than people, who's on Mount Hood studying a threatened native bumblebee. Then a local rabble rouser begins to rally support to build a commercial hunting camp that would destroy Mount Hood's pristine wilderness--the home of Jake's honeybees and Abigail's beloved bumblebees. And Jake, Abigail, and Flaco must come together to protect everything they hold dear. Full of warmth, big-hearted characters, and a celebration of nature in all its complexity, Bumblebee Season reminds us that human connection might just be the most powerful force there is.